Peer feedback or peer feedforward? Enhancing students' argumentative peer learning processes and outcomes. (24th January 2021) - Latifi, Saeed; Noroozi, Omid; Talaee, Ebrahim
Abstract: This study compared the effects of support for peer feedback, peer feedforward and their combination on students' peer learning processes, argumentative essay quality and domain‐specific learning. Participants were 86 BSc students who were randomly divided over 43 dyads. These dyads, in a two‐factorial experimental design, were assigned to four conditions including: peer feedback (n = 22), peer feedforward (n = 22), mixed (n = 20) and control group (n = 22) conditions. An online peer feedback environment named EduTech was designed which allowed us to implement various types of support in the form of question prompts. In this online environment, students were asked to write an argumentative essay on a controversial topic, to engage in peer learning processes and to revise their essay. Overall, the results showed that students in the three experimental conditions (peer feedback, peer feedforward and their combination) benefited more than students in the control group condition (without any support) in term of peer learning processes, argumentative essay quality and domain‐specific learning. However, there was no significant difference among the three experimental conditions. This implies that peer feedforward can be as important as peer feedback in collaborative learning environments which is often neglected both in theory and practice. Practitioner Notes What is already known about this topic? Writing argumentative essays is a common practice for higher education students in various disciplines which deal with controversial issues. Writing argumentative essay requires solid argumentation strategies which makes it a challenging task for higher education students. Additional instructional support is needed to help students write high‐quality argumentative essays. What this paper adds? Peer learning is a promising instructional strategy for improving students' argumentative essay writing and learning. Online support in the form of question prompts to guide students during peer learning can improve their argumentative essay writing and learning. Next to the peer feedback, peer feedforward is also a promising instructional approach to support students' argumentative essay writing and learning. Implications for practice and/or policy Given the positive effects of peer learning processes, the use of peer feedback and peer feedforward should be given more attention by teachers to support students write high‐quality argumentative essays for controversial issues. Teachers and educational designers should not only provide opportunities for students to engage in peer feedback processes (how I am doing?) but also in peer feedforward processes (where to next?).